Incorporating socio-economic effects and uncertain rainfall in flood mitigation decision using MCDA - Daksiya, Velautham (2017)
The decision making process in flood mitigation typically involves a number of factors reflecting flood severity, flood vulnerability and the cost of the mitigation measures, which implies that the decision framework needs to combine both social–economic parameters and flood extent prediction analysis. A socio-economic vulnerability index (SEVI) is developed here to represent social–economic factors and its use demonstrated within a multi-criteria decision analysis (MCDA) for assessing flood levee options for a central basin of Jakarta, Indonesia. The variables defining the SEVI are selected based on available national social–economic data reported for Indonesia with overlapping information removed using Pearson’s correlation analysis. Two different methods are used to further scale the SEVI which is developed along administrative boundaries into a Net SEVI which is dependent on the predicted flood hazard as resulting from the levee plan options while capturing uncertainty in the rainfall forecasting. The MCDA technique adopted uses criteria of Net SEVI, annual expected loss, graduality and levee construction cost for analyzing six different levee plans and with uncertainty in the rainfall incorporated. The Net SEVI thus specifically reflects the social–economic impact on the flood-affected population, and this approach thereby provides a higher degree of granularity in the flood mitigation decision process. The MCDA decision framework developed is general in that the Net SEVI can be applied for consideration of other flood mitigation strategies. Here, it is shown that the inclusion of the Net SEVI criteria changes the best choice levee plan decision to a higher protection level for the basin considered.